The Origins of the Peruvian Labor Movement, 1883-1919 - Blanchard, Peter, 1946- (Book collections on Project MUSE., 1982)
Monograph on the historical development of labour relations and the labour movement in Peru from 1883 to 1919 - considers labour disputes and their relationship with the political system during the early years of industrial development, and covers political ideologies, strikes, management attitudes, political leadership, economic conditions, rural workers in the labour movement, labour standards, etc. Bibliography pp. 195 to 203.